Microarray expression profile of circular RNAs in chronic thromboembolic pulmonary hypertension - Miao, Ran (Medicine (Baltimore), 2017)
BACKGROUND: Chronic thromboembolic pulmonary hypertension (CTEPH) is a rare but debilitating and life-threatening complication of acute pulmonary embolism. Circular RNAs (circRNAs), presenting as covalently closed continuous loops, are RNA molecules with covalently joined 3′- and 5′-ends formed by back-splicing events. circRNAs may be significant biological molecules to understand disease mechanisms and to identify biomarkers for disease diagnosis and therapy. The aim of this study was to investigate the potential roles of circRNAs in CTEPH. METHODS: Ten human blood samples (5 each from CTEPH and control groups) were included in the Agilent circRNA chip. The differentially expressed circRNAs were evaluated using t test, with significance set at a P value of < .05. A functional enrichment analysis for differentially expressed circRNAs was performed using DAVID online tools, and a Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis for target genes of miRNAs was performed using the R package clusterProfiler. Furthermore, miRNAs that interacted with differentially expressed circRNAs were predicted using the miRanda package. mRNAs that had clear biological functions and were regulated by miRNAs were predicted using miRWalk2.0 and then combined into a circRNA–miRNA–mRNA network. RESULTS: In total, 351 differentially expressed circRNAs (122 upregulated and 229 downregulated) between CTEPH and control groups were obtained; among these circRNAs, hsa_circ_0002062 and hsa_circ_0022342 might be important because they can regulate 761 (e.g., hsa-miR-942–5p) and 453 (e.g., hsa-miR-940) miRNAs, respectively. Target genes (e.g., cyclin-dependent kinase 6) of hsa-miR-942–5p were mainly enriched in cancer-related pathways, whereas target genes (e.g., CRK-Like Proto-Oncogene, Adaptor Protein) of hsa-miR-940 were enriched in the ErbB signaling pathway. Therefore, these pathways are potentially important in CTEPH. CONCLUSIONS: Our findings suggested that hsa_circ_0002062 and hsa_circ_0022342 may be key circRNAs for CTEPH development and that their targeted regulation may be an effective approach for treating CTEPH.